Optical measurement techniques for in-line process control in CdS/CdTe solar cell manufacturing - Kephart, Jason Michael, author; Sampath, Walajabad, advisor; Sites, James, committee member; Olsson, Anders, committee member (Colorado State University. Libraries, 2011)
CdS/CdTe solar cells have achieved gigawatt-scale commercial production at a lower cost than traditional crystalline silicon photovoltaics. With large-scale production of semiconductor devices, process control is critical to ensuring consistent quality. While there are many classes of materials characterization techniques including scanning probe, x-ray, electronic techniques, optical techniques are particularly promising for in-line structural characterization and process control. They are fast, non-contact, occupationally safe, precise, and can be performed immediately after film deposition to detect problems early in the manufacturing process. Two such optical techniques are examined here: spectroscopic ellipsometry and scanning white light interferometry. Spectroscopic ellipsometry consists of measuring the change in polarization of light reflected from a thin film structure. Fitting a model to the data provides structural information such as layer thickness and optical properties. Visually rough films can be a major obstacle to the use of ellipsometry, and processing options are explored to reduce roughness to acceptable levels. Ellipsometry has been shown to be accurate within 4% of thickness for the CdTe absorber layer and the CdS window layer can be measured accurately under the CdTe absorber for layers thicker than about 100 nm. Scanning white light interferometry (SWLI) uses the interference of reflected light from a surface to construct an extremely precise depth profile. This technique was examined for measurement of surface morphology and roughness as well as the measurement of film step heights, which could indicate whether or not the technique can be used for scribe metrology. Though the lateral resolution is limited by the use of optical microscopy, it has been shown that surface features can be resolved. Step height measurements match stylus profilometry very closely over a wide range of device thicknesses.